Penetration Testing Server Sistem Informasi Manajemen dan Website Universitas Kristen Petra - Richard Pangalila; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2015)
A developing organization need information technology in itsoperational activity. However what is often considered is how toensure that data saved in server is safe from unauthorized parties.Therefore, this thesis reviews how a person who is appointed as asecurity analyst do penetration testing in a system with variety toolsgiven and how the report can be understood from by people frommanagers to programmers. Besides giving the how-to knowledge,this thesis also reviews how secure is the organization under reviewin keeping their data safe from other parties who are not supposedto get access to important operational activity data.